Construction of Legal System for Maritime International Trade Financial Supervision Cooperation - Zhuo, Wuyang; Ding, Can; Xiong, Yuning; Peng, Jing (Journal of coastal research, 2020)
Zhuo, W.; Ding, C.; Xiong, Y., and Peng, J., 2020. Construction of legal system for maritime international trade financial supervision cooperation. In: Yang, Y.; Mi, C.; Zhao, L., and Lam, S. (eds.), Global Topics and New Trends in Coastal Research: Port, Coastal and Ocean Engineering. Journal of Coastal Research, Special Issue No. 103, pp. 143–146. Coconut Creek (Florida), ISSN 0749-0208. Under the background of financial globalization, the internationalization of financial market and financial activities has become an inevitable trend, and the financial crisis has universality and conductivity. Therefore, it is necessary to build a unified legal system of international trade and financial supervision cooperation at sea to protect the international financial supervision order. Due to the particularity of financial regulatory activities, the international community has not yet formed a unified legal system of international financial regulatory cooperation, and the urgent requirements of the globalization of financial activities for international financial regulatory cooperation make improving the legal framework of international financial regulatory cooperation become one of the important issues discussed by the international community today. The existing forms of international cooperation lay the foundation for the establishment of a unified legal mechanism for international cooperation in financial supervision. On the basis of the existing system, the current situation of the existing legal system in some countries and regions is analyzed. According to the analysis results, a new legal system for regulatory cooperation is constructed with the main research content of legal cooperation subjects, forms and contents. Through the form of empirical analysis, to verify the effectiveness of the designed legal system, the analysis results show that the system can effectively reduce the probability of financial events, which is conducive to the protection of financial order.